A comparison of three different gauge Quincke’s spinal needles in patients undergoing elective surgery under spinal anaesthesia: a prospective randomized study - Kaur, Kiranpreet; Singhal, Suresh K.; Mehla, Anu (International Journal of Research in Medical Sciences, 2019)
Background: The present study was conducted to compare three different Quincke’s spinal needles i.e. 23, 25 and 26 gauge in patients undergoing elective surgery under spinal anaesthesia (SA). Methods: The prospective randomized double-blind study was conducted on 150 male patients in the age group of 18-50 yrs., having physical status class I to II, scheduled for elective surgery under SA. Patients were randomly divided into three groups comprising 50 patients each. SA was administered using Quincke’s spinal needles of 23, 25 and 26 gauge in group 1, 2 and 3 respectively. Ease of insertion, number of attempts and time of appearance of CSF and incidence of PDPH was recorded in all the patients. Results: Ease of insertion was graded easy in 98%, 84% and 82% in group 1, 2 and 3 respectively. First attempt success rate was highest in group 1, (98%). Meantime for appearance of CSF beyond hub was maximum in group 3 i.e. 14.60±2.56 sec. Mild PDPH was reported in 6% and 2% patients after 24 hrs in group 1 and group 2 respectively. Conclusions: Finer spinal needle proved to be more dependable in generating less traumatic effect on the dura and preventing PDPH but are technically more difficult thus decreasing first attempt success rate.